Carrot cultivars under organic systems in the Angolan semi-arid region: agronomic performance and implications for family farming - Tito, Noe; Edjorge Francisco Van-Dúnen, Silvio; António, Sebastião; Baptista Zacarias, João; Raquel Regazzo, Jamile; o Wilson Mussalilo Alves, Faustino; Setsuko Kamimura, Eliana; Rossi, Fabrício (REVISTA DE AGRICULTURA, 2025)
This study aimed to evaluate the agronomic and economic performance of the carrot cultivars Kuroda and Dante under organic management in a semi-arid region of Angola. The experiment was carried out from March to July 2023 in a randomized complete block design with three replications, assessing yield, root morphological traits, germination rate, pest and disease incidence, soil parameters, and economic return. Kuroda showed higher productivity and profitability but greater susceptibility to carrot fly and leaf blight, whereas Dante exhibited lower yield yet superior resistance to pathogens and greater phytosanitary stability. It is concluded that organic carrot production is technically feasible in the Angolan semi-arid region when associated with agroecological practices and appropriate cultivar selection, contributing to the improvement of varietal selection and sustainable management in organic systems.